2010
DOI: 10.1086/653550
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 Different Regimens for Reactogenicity, Safety, and Immunogenicity of the Live Attenuated Oral Rotavirus Vaccine RIX4414 Coadministered with Oral Polio Vaccine in South African Infants

Abstract: The immune seroconversion response to the RIX4414 vaccine with 3 doses was not superior to the 2-dose regimen. There was no interference by either regimen with antibody response to oral polio vaccine, and RIX4414 was well tolerated when given with routine vaccinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 21 publications
2
27
1
Order By: Relevance
“…This evidence has been confirmed in the other studies conducted in the same population. 15,16 Peak rotavirus vaccine shedding was seen on Day 7 after Dose 1 of RIX4414 vaccine, which is similar to that reported in a study conducted in healthy infants. 27 The duration of rotavirus antigen excretion in HIV-positive infants appeared to be similar to that observed in healthy infants with prolonged shedding observed in only 1 infant in the RIX4414 vaccine group (rotavirus shedding beyond Day 42 post-Dose 3).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This evidence has been confirmed in the other studies conducted in the same population. 15,16 Peak rotavirus vaccine shedding was seen on Day 7 after Dose 1 of RIX4414 vaccine, which is similar to that reported in a study conducted in healthy infants. 27 The duration of rotavirus antigen excretion in HIV-positive infants appeared to be similar to that observed in healthy infants with prolonged shedding observed in only 1 infant in the RIX4414 vaccine group (rotavirus shedding beyond Day 42 post-Dose 3).…”
Section: Discussionsupporting
confidence: 85%
“…6,10,15 Currently, 2 oral doses of RIX4414 vaccine are administered at 2 and 4 months of age; however, at the time of this study, the number of doses to be administered to infants from low socioeconomic background and of very low age was still under evaluation. 16,17 In addition, if safety was to be evaluated in a developing country setting, the assessment of the longest possible regimen (ie, 3-dose schedule) was critical to consider. Therefore, the present study was conducted in asymptomatic or mildly symptomatic (clinical stages I and II according to WHO classification) 18 HIV-infected infants from South Africa to evaluate the safety, reactogenicity, and immunogenicity of 3 doses of RIX4414 vaccine as compared with placebo, when administered concomitantly with routine vaccines including oral polio vaccine (OPV).…”
mentioning
confidence: 99%
“…We used an exclusion/dropout rate of 30%, which was the exclusion/dropout rate in another trial (NCT00383903 [23]) conducted in South Africa around the same time period, to estimate the sample sizes of each group. Likewise, we were unable to determine the sample size for the immunogenicity cohort in Malawi from trial NCT00241644 [5, 18].…”
Section: Resultsmentioning
confidence: 99%
“…Administering rotavirus vaccines at younger ages could lower the immunogenicity of the vaccines, because of the potential for greater interference of maternal antibody 20 and enhanced replication of the oral poliovirus vaccine. 22,31,32 It will be important to undertake studies to assess the effectiveness of two doses of rotavirus vaccine administered at earlier ages than those at which they were administered in this study. The WHO's Global Advisory Committee on Vaccine Safety (GACVS) has reviewed the safety of the currently licensed rotavirus vaccines 33,34 and has concluded that in clinical trials of these vaccines, no association was seen between receipt of the vaccines and an increased risk of intussusception.…”
Section: Immunogenicitymentioning
confidence: 99%